Being fair, faring better : promoting equality of opportunity for marginalized Roma - Gatti, Roberta; Karacsony, Sandor; Anan, Kosuke; Ferré, Céline; De Paz Nieves, Carmen (Directions in development (Washington, D.C.). Human development., 2016)
In Central and Eastern European countries, inequalities for Roma families living in marginalized communities start early and are striking. Some of these inequalities reflect hard-wired family circumstances such as being born in poverty. Others reflect lack of opportunities such as limited access to those basic goods and services that are necessary not only for realizing one's potential in life, but also for living with dignity. Gaps between Roma and non-Roma widen over the lifecycle in a way that reinforces and perpetuates disadvantage and translates into significantly unequal outcomes, despite the fact that Roma report having similar aspirations to those of their non-Roma neighbors. Promoting equal opportunities for disadvantaged Roma is not only an imperative for societies that want to call themselves fair, but it is also a smart economic choice, especially in those countries where populations are aging rapidly. Investing early, with a particular emphasis on supporting healthy and cognitive development for disadvantaged Roma children, is likely to go a long way in promoting fair chances. However, leveling the playing field in childhood is likely not enough: disadvantaged Roma continue being exposed to unequal opportunities at key nodes in their lives, such as when pursuing education or when looking for a job. Therefore, it is as important that a broader set of policies address some of the circumstances in which a large share of Roma children grow up, including access to employment and decent living conditions for their families. Implementing interventions that help overcome these interrelated barriers will require strong ownership at the national level, coordinated policies across different ministries and government levels, and an integrated delivery system that is grounded in approaches that are customized to local conditions and implemented in a participatory manner. Good practices in Europe and elsewhere show that inclusion of the most disadvantaged - including many Roma - is possible and the current programming cycle for European Funds represents a unique opportunity to fund such interventions.